Simultaneous Photocatalytic Esterification and Addition Reaction of Fatty Acids in Kemiri Sunan (Reutealis trisperma sp.) Oil over CuO/TiO2 Catalyst - A Novel Approach - Athiek Sri Redjeki; Sukirno Sukirno; Slamet Slamet (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
A novel approach, namely photocatalytic esterification and addition reaction of unsaturated fatty acids using CuO/TiO2 catalyst has been investigated in kemiri sunan oil. The objectives of this study are to reduce the free fatty acid (FFA) content by using catalyst CuO/TiO2, characterization of the catalyst and the operation condition of reaction. The CuO/TiO2 catalyst was synthesized by the impregnation of TiO2 P25 powder with copper nitrate solution as a precursor and followed by calcination. The field emission scanning electron microscopy (FESEM), Energy Dispersive X-ray (EDX), X-ray Diffraction (XRD), and Transmission electron microscopes (TEM) result showed that copper oxide was highly dispersed on the TiO2 surface. The X-ray Photoelectron Spectroscopy (XPS) result showed that Cu is in the state of CuO (Cu2+), while Ti is in Ti4+ ( TiO2). The bandgap energy of CuO/TiO2 was smaller than TiO2 P25. It was found that the reactions conducted in the presence of CuO/TiO2 in a photoreactor under UV irradiation can perform esterification and addition reaction of the FFA, simultaneously. The optimum reduction of the FFA was under condition of 4% loading CuO/TiO2, 4 hours reaction time, 30:1 (mole/mole) methanol to oil ratio, 5% (w/w) catalyst amount. The conversion of FFA was at around 59%. The Gas Chromatography—Mass Spectrometry (GC-MS) results showed that the addition reaction of -eleostearic acid simultaneously occured at 100% conversion. Although the photocatalyst selectivity in FFA reduction was relatively low, but double bond reduction of -eleostearic acid (C18:3) was very high. The reduction of multiple double bond is considered as positive poin to improve the oxidative stability of the product. The simultaneous esterification and addition reactions mechanism has been proposed. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).